A transition to green ‘agrowth’ (Ökologisches Wirtschaften - Fachzeitschrift, 2020)
We need to debate in science, politics and wider society the option of stepping outside the futile framing of pro- versus anti-growth. Realizing there is a third way, namely an agrowth strategy, can help to overcome existing polarization and weaken political resistance against effective environmental and climate policies.